EFEKTIVITAS PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS PESERTA DIDIK KELAS V SEKOLAH DASAR - Tia, Septiana Sabila; Abung, Miranda; Destini, Frida; Syafrudin, Ulwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students’ mathematical creative thinking skills among fifth-grade elementary school students, which was attributed to teacher-centered learning practices and the limited use of innovative instructional materials. This study aimed to examine the effectiveness of Problem Based Learning (PBL)-based Student Worksheets (LKPD) in improving students’ mathematical creative thinking skills. A quantitative approach with a one-group pretest-posttest design was employed. The population consisted of 104 students, while 28 students were selected as the sample using purposive sampling technique. The research instruments included a mathematical creative thinking skills test and observation sheets as non-test instruments. All instruments had been tested for validity and reliability. Data were analyzed using prerequisite tests and the N-Gain test. The findings revealed that the N-Gain score was 0.77, which fell into the high category. This result indicated that the implementation of PBL-based LKPD was effective in enhancing students’ mathematical creative thinking skills. Therefore, PBL-based LKPD can be recommended as an innovative instructional material in elementary mathematics learning.